2018
DOI: 10.1177/1120672118805872
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early and late failure after goniotomy for primary pediatric glaucoma

Abstract: Purpose: To analyze the risk factors associated with early and late failure after goniotomy for primary pediatric glaucoma. Methods: A retrospective study was done on infants who underwent goniotomy as the initial surgical procedure for primary pediatric glaucoma, and had a follow-up period ⩾48 months after surgery. Early and late failures were defined as intraocular pressure ⩾18 mmHg or signs of glaucoma progression before and after the end of first year, respectively. Results: A total of 81 eyes of 47 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Moreover, in the present study, the operated eyes also had more severe glaucoma. Indeed, the initial mean IOP was 30.11 ± 7.08 mm Hg compared to 22 ± 4.5 mm Hg for Durr et al and 24.8 ± 3.86 mm Hg in the study by Quaranta et al It has been shown that higher pre-operative IOP can be a risk factor for failure of filtering surgery [ 16 , 17 , 18 ]. Our study found a success rate of 24% in patients who received needling or bubble filtration.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in the present study, the operated eyes also had more severe glaucoma. Indeed, the initial mean IOP was 30.11 ± 7.08 mm Hg compared to 22 ± 4.5 mm Hg for Durr et al and 24.8 ± 3.86 mm Hg in the study by Quaranta et al It has been shown that higher pre-operative IOP can be a risk factor for failure of filtering surgery [ 16 , 17 , 18 ]. Our study found a success rate of 24% in patients who received needling or bubble filtration.…”
Section: Discussionmentioning
confidence: 98%
“…We found a tendency towards greater risk of requiring more than one glaucoma procedure to control IOP in children operated before 3 months of age and in boys. Others have found that more severely affected children have an increased risk of failure (Al‐Hazmi et al 2005) and that boys are at greater risk of failure than girls (Hassanein et al 2018). The prevalence of PCG has been reported to be higher in boys by many studies (McGinnity et al 1987; de Silva et al 2011; Suri et al 2015) including in our population (Pedersen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,9,10,11,12,13 In addition, these angle procedures appear to have better outcomes in patients with PCG presenting between 1-24 months of age and have a worse prognosis in neonatal-onset PCG and in those with late-onset disease. 10,43,44…”
Section: Angiopoietin Receptor Tyrosine Endothelial Cell Kinase (Tek)mentioning
confidence: 99%